Psychosocial risk-factors of depression in adolescents: a cross-sectional study at tertiary hospital of southern Rajasthan - Vaishnav, Prerna; Seju, Lalit Kumar; Choudhary, Ravi; Bansal, Gargi; Singh, Milli (International Journal of Contemporary Pediatrics, 2025)
Introduction: Depression in adolescent is a growing global issue in India where world largest adolescent population with 253 million individuals resides. In 2024 global prevalence of depression among adolescent’s ranges from 6% to 21.3% according to World Health Organization. Family unrest contributes to risk of depression among adolescents. Methods: A Cross-sectional study was conducted on adolescents with non-cardiac chest pain between age 10-19 years. Research-designed questionnaire including demographic and risk factors was completed for each participant. PHQ 9 is patient health questionnaire tool of 9 items used to assess depressive symptoms. The participated adolescents who scored 15 and above were considered Depressed. Univariate analysis was performed to find out psychosocial risk factors. Adjusted odds ratio with 95% confidence intervals were derived. To test association of depression with socio-demographic factors we used PHQ-9 continuous scores as our main outcome. Results: Total 60 adolescents were assessed for depression using PHQ 9 severity assessment tool. 26.6% were found depressed using PHQ 9 score 15 and above. On Univariate analysis female gender, elder in age, belonging to lower socioeconomic class, dropped out of school, experiencing family conflicts and experiencing domestic abuse were significantly associated with depression. Living with single parents had 3.76 times higher risk of depression. 15.7% males were experiencing academic stress. Living arrangement, chronic illness, use of social media and relationship breakdown were not found significant risk factors. Conclusions: Depression is common in elderly female of Rajasthan belonging to lower socioeconomic class. Most common risk factors being family conflicts and domestic abuse. Academic stress in male adolescents living with parents was significant risk factor. There is urgent need to educate parents, to reduce parental pressure on academic performance and to stop early child marriage at rural level to save mental health of adolescents.